THE RELATIONSHIP BETWEEN THE STAR SYSTEM AND THE POPULAR CULTURE - Uygunkan, Sanem Bengü (PEOPLE: International Journal of Social Sciences, 2018)
This study includes an examination of the relationship between the popular culture and the star system. The main purpose of the study is to examine the interconnected relationship between popular culture and stars, in other words to examine and clarify the relation of the star system to the economic and cultural field. The star phenomenon has emerged in America at the end of the eighteenth century, when the middle class, who chose the theatre, ended up thinking of filming. The producers tried to make attractive theatrical actors play in movies and to make the audience close to the cinemas. The star system’s foundation has been laid, given the role of a goddess of love or idol to the actors or actresses (Yüksel, 2001, p.23-24). Popular culture is a usage and consumption culture. Other popular are used to create popular such as popular sports, athletes, artists, popular ideas and ideologies, behaviours, magazine heroes. Popular is packaged, and consumers take part in the popular popularization process by applying them to their lives (Erdoğan, 1999, p.3). A material or materialism is sold directly. It is indirect marketing through the media. Non-materials (ideologies) are also sold. Sales are legitimized by production relations. The star, a product of the consumer society, catches basic expectations. This is the inevitable meeting of commerce, art, goddess and merchandise. The star is convincing, makes people buy, and challenges time. It has an important feature of communication which is the "attraction". What is applicable to brands, also applies to stars (Seguêla, 1991, p. 55-58). Stars can be regarded as a popular product because they offer a combination of continuity, permanence and change. The stars can be related to the popular culture industry, with their own styles and the looks they follow, with the changes they make. This research is in the screening model. "The screening model is an approach aimed at describing the situation existed before or still existing as the way it is" (Karasar, 1995, p.77). This research aims to reveal the relationship between the concepts of star and popular culture. The information that will emerge as a result of this research can be enlightening for the studies in this area, as the concepts of "popular culture" and "star" can be important clues in the search for cultural, economic and social characteristics of societies.